2014
DOI: 10.1021/pr500294d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Digestion Technique, Protease, and Missed Cleavage Peptides in Protein Quantitation

Abstract: Quantitative determination of absolute and relative protein amounts is an essential requirement for most current bottom-up proteomics applications, but protein quantitation estimates are affected by several sources of variability such as sample preparation, mass spectrometric acquisition, and data analysis. Among them, sample digestion has attracted much attention from the proteomics community, as protein quantitation by bottom-up proteomics relies on the efficiency and reproducibility of protein enzymatic dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 21 publications
2
59
0
1
Order By: Relevance
“…Peptides possessing a lower potential for missed cleavage events are also advantageous (Lawless and Hubbard, 2012). This is pertinent given that in relative quantification analysis, up to 46% of peptides generated miscleaved events after in-solution trypsin digestion in E. coli (Chiva et al, 2014). For the peptide (AAVPDAVGK) selected for Na/K-ATPase quantification by BPh, the C-terminal lysine (K) is closely followed by an arginine (R), separated by a cysteine (C) residue [K.CR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides possessing a lower potential for missed cleavage events are also advantageous (Lawless and Hubbard, 2012). This is pertinent given that in relative quantification analysis, up to 46% of peptides generated miscleaved events after in-solution trypsin digestion in E. coli (Chiva et al, 2014). For the peptide (AAVPDAVGK) selected for Na/K-ATPase quantification by BPh, the C-terminal lysine (K) is closely followed by an arginine (R), separated by a cysteine (C) residue [K.CR.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a comparable study by , there was also an impact of peptide choice on OATP1B1 abundance using two of the same peptides as Terasaki et al (2014), yet little influence of peptide choice for P-glycoprotein (P-gp), breast cancer resistance protein (BCRP), OATP1B3, and OATP2B1 was observed. The digestion strategy employed might also influence the capacity to quantify protein abundances and to generate peptides that suffer missed cleavage by trypsin (Chiva et al, 2014). Studies comparing different proteomic approaches within a laboratory found that when comparing immunoblotting to stable isotope labeling of amino acids in culture/mammals (SILAC/SILAM) techniques, there was a reasonable agreement within the same samples to the absolute quantification (AQUA) method routinely employed (Kamiie et al, 2008;Qiu et al, 2013;Prasad and Unadkat, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation can also contribute to this variability, with proteins either quantified directly in whole cell/tissue lysate (Weiß et al, 2015;Wi sniewski et al, 2016) or in enriched subcellular fractions Gröer et al, 2013). In addition, differences in proteolytic strategies, efficiency of protein and peptide recovery and LC-MS analysis of peptides have also been suggested to introduce bias into abundance measurements (Chiva et al, 2014;Harwood et al, 2015). Other studies suggested that different analytical methods used in the same laboratory setting can generate reasonably consistent measurements (Qiu et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose we used an already published dataset from our group consisting of a mixture of thirty commercial proteins spiked in an E. coli background. 12 Briefly, five mixes were prepared in triplicate containing different ratios of the spiked-in proteins in the E. coli background, and the samples were subjected either to an in-solution or a filter-aided digestion with trypsin prior shotgun mass spectrometry acquisition. Initially we assessed the frequency, extend and reproducibility of the most common peptide chemical modifications from the E. coli proteome background for both the in-solution and filteraided original datasets (Table 1).…”
mentioning
confidence: 99%